Impact of Cloud, Rain, Humidity, and Wind Velocity on PV Panel Performance - Dawood Salman Hasan; Mansour S. Farhan; Haider alrikabi (Wasit Journal of Engineering Sciences)
Before the invention of solar panels, solar energy had been used for millions of years. To survive and increase many forms of life, people rely on sunlight. For example, use sunlight for warmth and have only recently begun to use the sun's energy to generate renewable and sustainable electricity. The widespread use of photovoltaic PV systems as a source of renewable energy-derived electricity has prompted researchers to investigate the factors that influence their performance. This paper presents an analytical study for assessing the performance of a 120 Wp PV module. This experiment was conducted at Al-Nasiriyah city ( 31.03 N, 46.16E ). At 180˚ south, and 45˚ elevation, the solar panel is omitted. Using solar panels, solar energy is converted into electrical energy that can power an entire building. The power production from the solar panel depends on several identified factors. In February and June, the solar panel tested the effect of cloud cover, rain,  relative humidity and wind velocity. On rainy and cloudy days, average power and irradiance are reduced by 93.32 %, 93.77 %, and 79.97 %, 77.34 %, respectively, when compared to power and irradiance on a clear day (8th February) 693 W/m2 and 76.55 W. Humidity has an inverse relationship with voltage, current, and power. It means that as humidity rises, the value of voltage, current, and power decreases. The performance of a solar panel is directly proportional to the wind velocity. The temperature is inversely proportional to wind velocity, i.e. as wind velocity increases, the temperature of the solar cell module decreases. The results of this study have been analyzed and discussed.